2015
DOI: 10.3390/ijerph121013350
|View full text |Cite
|
Sign up to set email alerts
|

Perceived and Objective Measures of Neighborhood Walkability and Physical Activity among Adults in Japan: A Multilevel Analysis of a Nationally Representative Sample

Abstract: Although associations between a person’s neighborhood and their health have been studied internationally, most studies have been limited to a few cities or towns. Therefore, we used a nationally representative sample to explore whether perceived and objective neighborhood walkability was associated with the physical activity of residents. Data were analyzed from the Japanese General Social Surveys of 2010 (n = 2395; 1114 men and 1281 women). Perceived walkability was scored using factor analysis for the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 33 publications
(53 reference statements)
4
30
1
1
Order By: Relevance
“…However, several recent studies have drawn attention to the divergent effects of objective and subjective dimensions of the built environment in explaining variations in walking behaviour (Hanibuchi et al 2015;Koohsari et al 2015). It has been suggested that both dimensions of the built environment should be included, as different associations have been found between the objective and subjective dimensions of the environmental features with walking behaviour (Ma et al 2015;Orstad et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent studies have drawn attention to the divergent effects of objective and subjective dimensions of the built environment in explaining variations in walking behaviour (Hanibuchi et al 2015;Koohsari et al 2015). It has been suggested that both dimensions of the built environment should be included, as different associations have been found between the objective and subjective dimensions of the environmental features with walking behaviour (Ma et al 2015;Orstad et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Aoyagi and Shephard suggested that taking <4000 daily steps was a simple objective criterion to determine whether someone was becoming housebound and taking >4000 steps suggested a lower risk of mental health disorders including depression . According to a previous study on the association between the environment and physical activity in Japanese adults, residents in rural areas walk less than those in urban areas, and physical access to shops, parks, and recreational facilities can improve residents’ physical activity and making them feel safe . In Odaka, the operation of grocery shops, medical and welfare facilities, and other institutions and the use of public transportations remained limited after the evacuation order was lifted.…”
Section: Discussionmentioning
confidence: 99%
“…43 According to a previous study on the association between the environment and physical activity in Japanese adults, residents in rural areas walk less than those in urban areas, and physical access to shops, parks, and recreational facilities can improve residents' physical activity and making them feel safe. 44 In Odaka, the operation of grocery shops, medical and welfare facilities, and other institutions and the use of public transportations remained limited after the evacuation order was lifted. Based on this, it can be assumed that in Okada, a large number of older returnees lead independent lives but have a low physical activity level.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…An environment’s perceived walkability can differ from its objectively assessed walkability [49], while research based on objective measures can identify different relationships between walking and the environment, and different pro-walking environmental factors, than can research based on subjective measures [50]. Other limitations of the study include the use of an unrepresentative sample, which makes extrapolating to the wider population of older adults difficult.…”
Section: Discussionmentioning
confidence: 99%